To the problem of observation of two-level tunneling states in supercooled liquids, glass-forming polymers, orientational glasses, and metallic glasses via configurational entropy - Kokshenev, Valery B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
From general perspectives, there is no conceptual gap between the structural and orientational glasses. Both kinds of glasses expose universal features during primary relaxation (Low Temp. Phys. 33, 617 (2007)). However, in spite of much efforts made to observe generic two-level systems (TLS) in polymers, organic liquids, and plastic crystals via thermodynamic measurements, no similarity unifying glass formers was established. Re-analyzing a number of experimental studies, it is revealed that no renormalization conditions imposedon occupation numbers of structural units, relaxing to the glass state, were taken into consideration by the experimentalists. In this study, the effective-cluster approach is applied to configurational (excess liquid-over-solid) entropy measured in both supercooled liquids and crystals through the heat capacity. As theresult, new relationships between the observable thermodynamic and dynamic characteristics are found formolecular liquids, polymers, and networks on the basis of available from the literature data. Thereby, new constraints of structure relaxation are shown to give strong evidence for the existence of TLS-type embryos of glassy structure in all studied glass formers.